Continuous-wave-tunable and passively Q-switched 2.9 µm Ho, Pr:LiLuF4 lasers. (30th November 2018) - Liu, Shande; Nie, Hongkun; Zhang, Baitao; Zhang, Peixiong; Sun, Xiaoli; Yan, Bingzheng; Li, Guoru; Wang, Yiran; Liu, Junting; Shi, Bingnan; Hang, Yin; He, Jingliang
Abstract: A wavelength tuning experiment of a continuous-wave Ho, Pr:LiLuF4 bulk laser operating at 2900 nm has been demonstrated for the first time. Two wavelength-tunable bands in the ranges of 2830–2902 nm and 2945–2956 nm were obtained. In addition, by using a semiconductor saturable absorber mirror, a high-peak-power passively Q-switched operation was realized. The shortest pulse width was 395 ns with a repetition rate of 7.29 kHz, corresponding to a peak power of 51.1 W. The results indicate the potential of Ho, Pr:LLF crystals for continuous-wave-tunable and passively Q-switched lasers operating at ~3.0 µ m.